172 Effects of Dietary Valine, Isoleucine, and Tryptophan Supplementations to Diets Containing Excess Leucine from Corn Protein on Growth Performance of Growing Pigs - Kwon, Woongbi Bi (J Anim Sci, 2021)
An experiment was conducted to test the hypothesis that addition of Val, Ile, or Trp alone or in combination will reduce the negative effects of excess Leu in diets for growing pigs. A total of 288 growing pigs (28.6 ± 2.5 kg) were randomly assigned to 1 of 9 dietary treatments in a randomized complete block design. There were 2 barrows and 2 gilts in each pen and 8 replicate pens per treatment. A control diet based on corn and soybean meal and 8 diets based on corn and a high-protein corn product (48% crude protein) with 2 levels of crystalline L-Val (0 or 0.10%), L-Ile (0 or 0.10%), and L-Trp (0 or 0.05%) were formulated. The crystalline L-Val, L-Ile, and L-Trp increased standardized ileal digestible (SID) Val:Lys from 70 to 80%, SID Ile:Lys from 53 to 63%, and SID Trp:Lys from 18 to 23%, respectively. All diets were formulated to contain 1.00% SID Lys and the 8 diets containing corn protein contained 171% SID Leu:Lys. Individual pig weights were recorded at the beginning and at the conclusion of the 28-d experiment. Data were analyzed using the PROC MIXED of SAS with a pen as the experimental unit. Diet was the fixed effect and block and replicate within block were random effects. Results indicated that final body weight and average daily gain were not different between pigs fed the control diet and pigs fed the diet with Val and Trp addition, but greater (P < 0.001) than for pigs fed the diet with Val addition, Ile addition, Trp addition, Val and Ile addition, Ile and Trp addition, or Val, Ile, and Trp addition (Table 1). In conclusion, addition of Val and Trp to diets with excess Leu may prevent negative effects of excess Leu in diets for growing pigs. [Image: see text]